"How can you be Muslim? You look like you’re Greek!": investigating Muslim women’s experiences of islamophobia in Greece - Verousi, Christina (The Palgrave handbook of gendered Islamophobia, 2024)
Existing studies indicate that Muslim women are at a heightened risk of Islamophobic victimisation, their religious attire further enhancing their visibility. Correspondingly, their vulnerability is amplified by virtue of their gender and perceived gendered identity, both in the Islamic world and in the West. The same is true in the context of Greece, a predominately Christian Orthodox country, where research into Islamophobia has been scant. Drawing on in-depth, qualitative interviews with Muslim women, this study sets out new findings that both build on existing knowledge about gendered Islamophobia, while illustrating the unique dimensions and impacts of Islamophobia in a vastly under-researched setting. More specifically, this chapter first explores the existing scholarly canon relating to gendered Islamophobia and subsequently sets out new and original findings considering the nature and scope of Islamophobic victimisation in Greece directed towards Muslim women. In doing so, this chapter makes timely and significant contribution to what is currently an embryonic body of work.